Configuring Masculinity in Theory and Literary Practice - Horlacher, Stefan (Brill, 2015)
Configuring Masculinity in Theory and Literary Practice combines a critical survey of the most current developments in the emergent field of Masculinity Studies with both a historical overview of how masculinity has been constructed within British Literature from the Middle Ages to the present and a special focus on developments in the 20th and 21st centuries. The volume combines seminal articles on the most important concepts in Masculinity Studies by acknowledged experts such as Raewyn Connell, Todd Reeser, and Richard Collier with new and innovative analyses of key British literary texts combining Literary and Cultural Studies approaches with those currently deployed in Masculinity Studies, Gender Studies, Legal Studies, Postcolonial Studies as well as methodologies derived from sociology.
Description based on print version record.
KU Select 2019: HSS Backlist Books
Keywords: Literary Criticism / Subjects & Themes; Literary Criticism / European / English, Irish, Scottish, Welsh; Literature -- History and criticism; Electronic books